2019
DOI: 10.1111/jocn.15076
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and fatigue in newly graduated nurses—Experiences and strategies for handling shiftwork

Abstract: Aims and objectives To explore newly graduated nurses' strategies for, and experiences of, sleep problems and fatigue when starting shiftwork. A more comprehensive insight into nurses' strategies, sleep problems, fatigue experiences and contributing factors is needed to understand what support should be provided. Background For graduate nurses, the first years of practice are often stressful, with many reporting high levels of burnout symptoms. Usually, starting working as a nurse also means an introduction to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 46 publications
4
39
0
3
Order By: Relevance
“…Furthermore, because the healthcare workers still had to work a certain number of days, they still participated in moderate physical activity and experienced moderate not excessive fatigue, which might have led to better sleep quality [ 21 ]. Another possible reason was that an appropriate work time ensured the proficiency of clinical work [ 22 ], which was also supported by another observation in this study that the years of work experience were negatively associated with sleep quality. This may reduce the degree of anxiety and fear regarding 2019-nCoV infection and improve sleep quality.…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, because the healthcare workers still had to work a certain number of days, they still participated in moderate physical activity and experienced moderate not excessive fatigue, which might have led to better sleep quality [ 21 ]. Another possible reason was that an appropriate work time ensured the proficiency of clinical work [ 22 ], which was also supported by another observation in this study that the years of work experience were negatively associated with sleep quality. This may reduce the degree of anxiety and fear regarding 2019-nCoV infection and improve sleep quality.…”
Section: Discussionsupporting
confidence: 73%
“…Second, identifying the individuals most prone to developing sleep problems could allow managers to select a subgroup of workers to be assigned to specific prevention and treatment programs. For instance, sleep hygiene interventions adapted to the atypical sleep condition could be implemented (Shriane et al, 2020), especially among the most at-risk categories, such as newly graduated nurses (Epstein et al, 2020).…”
Section: "Fixed" Individual Factorsmentioning
confidence: 99%
“…Qiao et al reported that HIV/AIDS healthcare workers with low job satisfaction and poor sleep situation had higher burnout (Qiao et al, 2016). Fatigue has also been linked to burnout (Epstein et al, 2019). Ortiz indicated that NGNs lacked professional confidence and clinical skills (Ortiz, 2016).…”
Section: Introductionmentioning
confidence: 99%